2014
DOI: 10.1038/ngeo2247
|View full text |Cite|
|
Sign up to set email alerts
|

Global assessment of trends in wetting and drying over land

Abstract: Changes in the hydrological conditions of the land surface have substantial impacts on society1, 2. Yet assessments of observed continental dryness trends yield contradicting results3, 4, 5, 6, 7. The concept that dry regions dry out further, whereas wet regions become wetter as the climate warms has been proposed as a simplified summary of expected8, 9, 10 as well as observed10, 11, 12, 13, 14 changes over land, although this concept is mostly based on oceanic data8, 10. Here we present an analysis of more th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
582
9
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 717 publications
(630 citation statements)
references
References 23 publications
36
582
9
3
Order By: Relevance
“…In the last decades, the severity of droughts in the IP has increased, together with an increased tendency for dryness and decrease of vegetation cover, due to the higher atmospheric evaporative demand [28,37]. These agree with the findings of Greve et al [38] that identified the Southwest of the IP as one hot spot of the pattern "dry gets drier." The need for a deeper knowledge of drought frequency, duration, and intensity over the IP during the last century is reinforced by the findings by Hoerling et al [39] using Sea Surface Temperature data that have shown that the period of 1970-2010 over the Mediterranean region was considered drier when compared with 1901-1970.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…In the last decades, the severity of droughts in the IP has increased, together with an increased tendency for dryness and decrease of vegetation cover, due to the higher atmospheric evaporative demand [28,37]. These agree with the findings of Greve et al [38] that identified the Southwest of the IP as one hot spot of the pattern "dry gets drier." The need for a deeper knowledge of drought frequency, duration, and intensity over the IP during the last century is reinforced by the findings by Hoerling et al [39] using Sea Surface Temperature data that have shown that the period of 1970-2010 over the Mediterranean region was considered drier when compared with 1901-1970.…”
Section: Introductionsupporting
confidence: 82%
“…Several authors have discussed the role of including ET 0 in the trend analysis of droughts at global [25,31,32,38,56], continental [35,67], and national or regional scales [68,69]. Using distinct datasets and/or different drought indices for various regions of the Mediterranean basin and considering shorter periods, several authors identified colder/wetter and warmer/dryer periods over different regions [22,25,44,70,71].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking to the future, it will become even more important to separately resolve VPD and soil moisture effects on ecosystem functioning. VPD is highly sensitive to changes in air temperature and is thus expected to rise globally in the future 1,20 . On the other hand, projected changes in precipitation and soil moisture are less certain, more spatially variable, and smaller in relative magnitude 21 .…”
mentioning
confidence: 99%
“…The canonical description of precipitation changes under increasing CO 2 has been that the "wet get wetter" and the "dry get drier" [19], however this is a poor characterization of the change in pattern of precipitation change over land observed in the historical period [20], or predicted for the future [21][22][23].…”
Section: Supply and Demandmentioning
confidence: 99%